Abundance of Phytoplankton in Vannamei Shrimp (Litopenaeus vannamei) Farming Pond at the Center for Brackish Water Aquaculture Fisheries (BBPBAP) Jepara - Anja Asmarany (Journal of Aquaculture Development and Environment, 2022)
Vannamei shrimp (Litopenaeus vannamei) is one of the commodities that is a priority in aquaculturedevelopment activities in Indonesia. The success of vannamei shrimp culture is influenced by variousfactors such as fry quality, feed quality, land carrying capacity, application of biosecurity and goodwater quality management. Water quality is closely related to the phytoplankton community containedin a waters. This study aims to analyze the abundance and dominance of plankton species found inpond waters. Monitoring the abundance of phytoplankton was carried out in 4 plots of vannameishrimp aquaculture ponds at the Brackish Water Aquaculture Fisheries Center (BBPBAP) Jepara,namely plots A51, A51, A61 and A62. Identification and calculation of phytoplankton cells werecarried out using a haemocytometer and Sedgwick. The results of the analysis showed that the highestabundance of phytoplankton was found in plots A61 at week 9 with a cell number of 36.73 x 106cells/L, while plots A51, A52 and A62 decreased. Overall plot A62 had better water quality conditionswhen compared to plots A51, A52 and A61 indicated by the phytoplankton abundance value of 34.63x 106 cells/L at week 9 and the dominance index of green algae, namely D > 0.5.